Theoretical Study on the Transition-Metal Oxoboryl Complex: M–BO Bonding Nature, Mechanism of the Formation Reaction, and Prediction of a New Oxoboryl Complex - Zeng, Guixiang; Sakaki, Shigeyoshi (Inorganic chemistry, 2012)
The Pt–BO bonding nature and the formation reaction of the experimentally reported platinum(II) oxoboryl complex, simplified to PtBr(BO)(PMe3)2, were theoretically investigated with the density functional theory method. The BO– ligand was quantitatively demonstrated to have extremely strong σ-donation but very weak dπ-electron-accepting abilities. Therefore, it exhibits a strong trans influence. The formation reaction occurs through a four-center transition state, in which the Bδ+–Brδ− polarization and the Br → Si and O pπ → B pπ charge-transfer interactions play key roles. The Gibbs activation energy (ΔG°⧧) and Gibbs reaction energy (ΔG°) of the formation reaction are 32.2 and −6.1 kcal/mol, respectively. The electron-donating bulky phosphine ligand is found to be favorable for lowering both ΔG°⧧ and ΔG°. In addition, the metal effect is examined with the nickel and palladium analogues and MBrCl[BBr(OSiMe3)](CO)(PR3)2 (M = Ir and Rh). By a comparison of the ΔG°⧧ and ΔG° values, the M–BO (M = Ni, Pd, Ir, and Rh) bonding nature, and the interaction energy between [MBrCl(CO)(PR3)2]+ and BO– with those of the platinum system, MBrCl(BO)(CO)(PR3)2 (M = Ir and Rh) is predicted to be a good candidate for a stable oxoboryl complex.